ChemInform Abstract: Rapid Synthesis and Enhanced Thermoelectric Properties of Ba8Cu6Ge8xSi40‐8x (x = 0, 1, 2, 3) Alloys Prepared Using High‐Temperature, High‐Pressure Method. Issue 32 (22nd July 2016) - Sun, Bing; Jia, Xiaopeng; Huo, Dexuan; Sun, Hairui; Zhang, Yuewen; Liu, Binwu; Liu, Haiqiang; Kong, Lingjiao; Liu, Baomin; Ma, Hongan
Abstract: The title clathrates are prepared by hot press sintering of stoichiometric amounts of Si, Ge, Cu, and BaSi2 (China‐type cubic high pressure apparatus, 3 GPa, 1125 K, 30 min).